STYLISTIC ANALYSIS OF PERSUASIVE TECHNIQUES IN MALE SKINCARE ADVERTISING ON INSTAGRAM - Rewin Darmawan; Rohmani Nur Indah (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study explores the persuasive techniques employed in advertisements for male skincare products on Instagram. Specifically, it examines the types and functions of these techniques as used in Instagram captions from beauty product accounts, focusing on the official L’Oréal Paris account. The research data were sourced from several Instagram captions on the official L’Oréal Paris account. A descriptive method was used to analyze the data, drawing on Lamb's theory (2019) and Keraf's theory (2004). The dataset comprises 24 Instagram captions advertising male skincare products on the L’Oréal Paris official account. Lamb's theory (2019) offers a framework for analyzing emotive and inclusive language, while Keraf’s theory (2004) emphasizes identification, suggestion, and compensation techniques. The analysis reveals that the persuasive techniques identified using Lamb's theory (2019) include emotive language (8 instances), everyday/colloquial language (7), inclusive language (1), evidence (3), rhetorical questions (2), appeals (2), and hyperbole (1). Meanwhile, applying Keraf’s theory (2004) identified techniques such as identification (8 instances), suggestion (13), and compensation (3). The findings indicate that emotive language and suggestion are the most frequently employed persuasive techniques, emphasizing the emotional and suggestive appeals in L’Oréal Paris’s male skincare advertisements. Future research could explore additional persuasive theories or examine a broader range of product categories to gain a more comprehensive understanding of advertising strategies on social media.